2011
DOI: 10.1371/journal.pone.0020893
|View full text |Cite
|
Sign up to set email alerts
|

Novel Arenavirus Sequences in Hylomyscus sp. and Mus (Nannomys) setulosus from Côte d'Ivoire: Implications for Evolution of Arenaviruses in Africa

Abstract: This study aimed to identify new arenaviruses and gather insights in the evolution of arenaviruses in Africa. During 2003 through 2005, 1,228 small mammals representing 14 different genera were trapped in 9 villages in south, east, and middle west of Côte d'Ivoire. Specimens were screened by pan-Old World arenavirus RT-PCRs targeting S and L RNA segments as well as immunofluorescence assay. Sequences of two novel tentative species of the family Arenaviridae, Menekre and Gbagroube virus, were detected in Hylomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 46 publications
5
78
0
1
Order By: Relevance
“…In order to avoid taxonomic misidentifications, all M. minutoides specimens used in this study were confirmed molecularly based on the sequences of the cytochrome b gene [Veyrunes et al, 2005;Fichet-Calvet et al, 2009Coulibaly-N'Golo et al, 2011;Britton-Davidian et al, 2012;this study]. A total of 72 females and 5 males from various localities distributed in 3 countries (Guinea, Ivory Coast and Ghana) was analyzed.…”
Section: Specimensmentioning
confidence: 99%
“…In order to avoid taxonomic misidentifications, all M. minutoides specimens used in this study were confirmed molecularly based on the sequences of the cytochrome b gene [Veyrunes et al, 2005;Fichet-Calvet et al, 2009Coulibaly-N'Golo et al, 2011;Britton-Davidian et al, 2012;this study]. A total of 72 females and 5 males from various localities distributed in 3 countries (Guinea, Ivory Coast and Ghana) was analyzed.…”
Section: Specimensmentioning
confidence: 99%
“…Still, two novel arenavirus sequences were found by advanced RT/PCR; with tentative names Menekre (MENV) and Gbagroube (GBAV) viruses, those sequences were detected in Hylomyscus sp . and Mus (Nannomys) setulosus , respectively [45]. Notably, GBAV sequence was closely related to LASV, while MENV sequence clustered with IPPYV-MOBV-MOPV.…”
Section: Lassa Virus Diversity and Novel African Arenavirusesmentioning
confidence: 99%
“…Each rodent-borne arenavirus species appears to be primarily associated with one (or a few closely related) rodent species, compatible with the longterm co-divergence of these viruses with their hosts (Gonzalez et al, 2007). To date, 25 established arenaviruses have been identified worldwide, largely from the New World, as well as several newly discovered viruses whose taxonomic status has not yet been confirmed by the International Committee on Taxonomy of Viruses (Salvato et al, 2011;Coulibaly-N'Golo et al, 2011;Kronmann et al, 2013;Stenglein et al, 2012;Bodewes et al, 2013;Hetzel et al, 2013). These viruses form two phylogenetic groups according to their geographic origins -the New World and the Old World arenaviruses -although Lymphocytic choriomeningitis virus (LCMV) is more globally distributed.…”
Section: Introductionmentioning
confidence: 99%